2008
DOI: 10.1534/genetics.107.082933
|View full text |Cite
|
Sign up to set email alerts
|

Neofunctionalization of Duplicated Genes Under the Pressure of Gene Conversion

Abstract: Neofunctionalization occurs when a neofunctionalized allele is fixed in one of duplicated genes. This is a simple fixation process if duplicated genes accumulate mutations independently. However, the process is very complicated when duplicated genes undergo concerted evolution by gene conversion. Our simulations demonstrate that the process could be described with three distinct stages. First, a newly arisen neofunctionalized allele increases in frequency by selection, but gene conversion prevents its complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 32 publications
(30 reference statements)
1
47
0
Order By: Relevance
“…Second, gene conversion can contribute to neofunctionalization, since beneficial mutations can be shared and also, novel combinations of allelic sequences can be created. In a theoretical model, Teshina and Innan have explored another interesting effect of gene conversion by which it counteracts neofunctionalization (Teshima and Innan, 2008). A DNA sequence conferring a novel function can be converted back to the ancestral sequence by gene conversion.…”
Section: Concerted Evolution By Gene Conversionmentioning
confidence: 99%
“…Second, gene conversion can contribute to neofunctionalization, since beneficial mutations can be shared and also, novel combinations of allelic sequences can be created. In a theoretical model, Teshina and Innan have explored another interesting effect of gene conversion by which it counteracts neofunctionalization (Teshima and Innan, 2008). A DNA sequence conferring a novel function can be converted back to the ancestral sequence by gene conversion.…”
Section: Concerted Evolution By Gene Conversionmentioning
confidence: 99%
“…This might take time, so it is important to know whether this temporarily neofunctioned gene (pink box) can be maintained for a sufficiently long time, during which the two genes can accumulate mutations. Innan (2003b) proposed a two-locus model of this process, and found that the temporal state can be stably maintained when the power of selection to eliminate deleterious gene conversion is sufficiently stronger than the pressure of homogenization by gene conversion (see also Teshima and Innan 2008). In the model, it is assumed that chromosomes having two different alleles (i.e., AB and BA) are advantageous over those with a single kind (i.e., AA and BB).…”
Section: The Fates Of Duplicated Genes Under the Pressure Of Gene Conmentioning
confidence: 99%
“…The likely reason appears to be that gene conversion was at some point inactivated in the first introns of ph-p and ph-d, because of drastic sequence differences caused by insertion/deletion events (43). As a result, the first intron of ph-p (which is much larger than that of ph-d) contains several regulatory elements that may be potential targets of selection (in that they can escape the counteracting force of gene conversion).…”
Section: Significance Of the Selective Sweep And Neofunctionalizationmentioning
confidence: 99%